A Numerical Investigation of Rotating Instability in Steam Turbine Last Stage - Zhang, L; He, L; Stueer, H (2013)
The unsteady flow phenomenon (identified as rotating instability) in the last stage of a low-pressure model steam turbine operated at very low mass flow conditions is numerically studied. This kind of instability has been observed previously in compressors and can be linked to the high structural stress levels associated with flow-induced blade vibrations. The overall objective of the study is to enhance the understanding of the rotating instability in steam turbines at off design conditions. A numerical analysis using a validated unsteady nonlinear time-domain CFD solver is performed. The 3D solution captures the massively separated flow structure in the rotor-exhaust region and the pressure ratio characteristics around the rotor tip of the test model turbine stage in good comparison with the experiment. A computational study with a multi-passage whole annulus domain on two different 2D blade sections is subsequently carried out. The computational results clearly show that a rotating instability in a turbine blading configuration can be captured by the 2D model. The frequency and spatial modal characteristics are analyzed. The simulations seem to be able to predict a rotating fluid dynamic instability with the similar characteristic features to those of the experiment. In contrast to many previous observations, the results for the present configurations suggest that the onset and development of rotating instabilities can occur without 3D and tip-leakage flows, although a quantitative comparison with the experimental data can only be expected to be possible with fully 3D unsteady solutions. © 2013 American Society of Mechanical Engineers.